Does a person-environment-fit promote the academic achievement of hearing-impaired students in Malaysian polytechnics? the mediating effects of satisfaction and adjustment - Azizan, Che’ Rozaniza; Roslan, Samsilah; Abdullah, Maria Chong; Asimiran, Soaib; Zaremohzzabieh, Zeinab; Ahrari, Seyedali (Multidisciplinary Digital Publishing Institute, 2021)
(1) This study investigates the influence of a person-environment-fit on academic achievement and examines mediating effects of adjustment and satisfaction on this relationship; (2) Methods: Data were collected from a sample of 195 hearing-impaired students from five polytechnics in Malaysia that offered the Special Skills Certificate program; (3) Results: Results revealed that the two constructs of the person-environment approach: personality-major fit and needs-supplies fit were positively associated with academic achievement. The adjustment was found to mediate this relationship. Taken together, these results signal that the person-environment constructs contribute to the academic achievement of hearing-impaired students and that adjustment is instrumental in elucidating this relationship; (4) Conclusions: The finding adds to the data, indicating that the person-environment-fit is a possible model of inclusion for hearing-impaired students and also provides initial data about the functioning of hearing-impaired students in Malaysian polytechnics.